2007
DOI: 10.1002/mde.1421
|View full text |Cite
|
Sign up to set email alerts
|

Stadium attendance and television audience demand in English league football

Abstract: Demand studies of professional team sports have traditionally focused on stadium attendance; however, advances in broadcasting mean that teams generate revenue from stadium goers and broadcasters alike. Previous studies of demand have focused on stadium attendance and television audiences, but none have assessed the demand for match-day attendances and demand by television audiences jointly. This study models match-day attendances and television audiences using data from tier-two of English league football. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(124 citation statements)
references
References 18 publications
4
111
1
2
Order By: Relevance
“…Forrest, Simmons, and Buraimo (2005), for example, reported that the coefficient associated with the difference in relative wages has a negative and statistically significant sign. In Buraimo (2008) and Buraimo and Simmons (2015), the coefficients associated with the absolute difference in relative wages are not statistically significant, even though this variable is relevant in determining the selection of matches to be broadcasted. Cox (2015) modelled the outcome uncertainty using the difference in win probabilities; when statistically significant, the associated coefficient is negative, supporting the UOH.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Forrest, Simmons, and Buraimo (2005), for example, reported that the coefficient associated with the difference in relative wages has a negative and statistically significant sign. In Buraimo (2008) and Buraimo and Simmons (2015), the coefficients associated with the absolute difference in relative wages are not statistically significant, even though this variable is relevant in determining the selection of matches to be broadcasted. Cox (2015) modelled the outcome uncertainty using the difference in win probabilities; when statistically significant, the associated coefficient is negative, supporting the UOH.…”
Section: Resultsmentioning
confidence: 93%
“…Then, combined_market is introduced to take into account the market size effects, as used by Cairns (1987), Buraimo andSimmons (2006), Tainsky (2010), and Caruso and Di Domizio (2015a): we expect a larger audience for games involving teams with larger local fan bases. It is computed as follows:…”
Section: The Italian Football Broadcasting Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Forrest et al (2005) also mainly focus on outcome uncertainty, and use their model to support the broadcasters' choice of which matches to televise in the English Premier League. Buraimo (2008) models the audience ratings for the second tier of English league soccer, taking into account team form, player talent, outcome uncertainty, and atmosphere. Further, Feddersen and Rott (2011) identify determinants of demand for televised matches of the German national team.…”
Section: Introductionmentioning
confidence: 99%